A novel paradigm for the fabrication of highly uniform nanowire arrays using residual stress-induced patterning. Issue 24 (2nd June 2016) - Zhao, Zhi; Wang, Nan; Nan, Hanqing; Shen, Li; Durkan, Colm; He, Ximin
Abstract : A residue-free, one-step method for the fabrication of 1-D materials with highly tunable geometric parameters. Abstract : Patterned low-dimensional (1-D or 2-D) nanomaterials have recently drawn tremendous attention due to their unique properties. To realize their wide range of potential applications in electronics, sensing and energy storage, it is critical yet still challenging to fabricate highly uniform 1-D material arrays ( e.g. nanowire arrays) that simultaneously feature high resolution, large scale and tunable geometric parameters. Herein, we report a novel method for the fabrication of large-area, highly aligned nanowire arrays using the combination of one-step residual-free nanopatterning via pressure-induced instabilities and low-temperature hydrothermal synthesis. We demonstrate that the fabrication of highly tunable, vertically aligned single-crystal zinc oxide (ZnO) nanowire (NW) arrays can be achieved on arbitrary substrates. The height, diameter, locations and orientations of ZnO NWs are precisely controlled through the spatial confinement effect of the spontaneously formed polymer masks. The high qualities of the as-prepared NW arrays have been revealed by the systematic characterization of the morphology, crystallinity, and electronic properties of single ZnO NWs. Conductive atomic force microscopy (cAFM) measurements show Schottky barrier characteristics in the I – V curves and a clear registration of the detected current signal with individual NWs. Mechanically-induced currents are observed to change with the deformation magnitude of NW, directly indicating the generation of piezoelectricity. This work provides a novel universal paradigm for patterned 1-D nanomaterial fabrication and opens up unprecedented opportunities for more design innovations and applications in nano-devices.